Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s11605-015-3068-9
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Readmissions for Patients with Inflammatory Bowel Disease (IBD) After Colorectal Surgery

Abstract: Black patients with IBD have an increased risk for readmission after colorectal surgery. Efforts to reduce readmissions need to target not only well-studied risk factors such as postoperative complications, but also investigate non-NSQIP-measured elements such as social and behavioral determinants of health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Even after multivariable analysis, rates of extended HLOS were between 15% and 20% higher for African‐Americans and ‘Others’. These data are indirectly supported by previous studies such as that of Gunnells et al , who showed that African‐American patients with IBD have higher rates of 30‐day readmission after elective surgery, and Montgomery et al , who reported that African‐American patients with IBD undergoing surgery had significantly higher complication rates even after multivariable analysis.…”
Section: Discussionsupporting
confidence: 79%
“…Even after multivariable analysis, rates of extended HLOS were between 15% and 20% higher for African‐Americans and ‘Others’. These data are indirectly supported by previous studies such as that of Gunnells et al , who showed that African‐American patients with IBD have higher rates of 30‐day readmission after elective surgery, and Montgomery et al , who reported that African‐American patients with IBD undergoing surgery had significantly higher complication rates even after multivariable analysis.…”
Section: Discussionsupporting
confidence: 79%
“…35 Given the structure of the NRD, we were also unable to evaluate provider factors that may have contributed to readmission, including early discharge from the index hospitalization or treatment plans that may have led to worse outcomes including readmission. While future approaches to decreasing readmission will likely require multidisciplinary approaches, a continued focus on provider decision making during the hospitalization and discharge planning will remain a key point in improving outcomes among hospitalized patients with IBD.…”
Section: Discussionmentioning
confidence: 99%
“…In one study which used the targeted colectomy dataset from 2012 to 2013, black race was associated with a 60% higher postoperative readmission rate than white race after IBD surgery when controlling for other factors, demonstrating the effects of race and possibly socioeconomic status on outcomes in IBD surgery. 36 Arsoniadis et al further showed that African Americans had a higher complication rate after surgery for CD and that this disparity only disappeared when controlling for comorbidities and ASA score, underscoring some of the health issues associated with racial disparities. 37 The inadequacies of NSQIP, in its current state, are laid most bare when analyzing the outcomes after ileal pouchanal anastomosis (IPAA) surgery for CUC.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%